Sodality in Peri-Urban Community Empowerment: Perspective of Development Communication and Extension Science - Sumardjo Sumardjo; Adi Firmansyah; Leonard Dharmawan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
Tjondronegoro's concept of sodality is gaining momentum to be applied in a broader context. Sodality is relevant to participatory approaches in community development, extension/empowerment, and development communication. This study aims to answer how the role of sodality is in the empowerment of peri-urban communities from communication and extension development sciences. This research method uses a participatory action study by placing the researcher to live with the community. Sodality can be interpreted as the life force of a unique community unit. However, without any family relationship, they are bound by a synergy of interest relations without eliminating the primary relationship. In the context of empowerment, the bonds in sodality are colored more with interest in achieving life necessities among community members. Thus, in peri-urban communities, sodality is closer to the meaning of social capital, which effectively strengthens the community's efforts to live a life together, both with internal and external parties. The Tjondronegoro version of the concept of sodality in the current era is not only for the smallest community unit in the community territory, but it can be strengthened by the meaning of a synergy of interests in meeting the needs of a community.